An intraorbital foreign body with paradoxical radiological interpretations to dive in or not? a surgeon’s dilemma - Deuri, Arup; Dam, Bikram; Kumar, Naveen (International Journal of Research in Medical Sciences, 2020)
A 10-year-old girl presented to our O.P.D. with intra-orbital trauma. On radiological workup following admission, USG B Scan, MRI Brain and 3D reconstructed faciomaxillary imaging were indeterminate for presence of foreign body, whereas CT scan showed a hyperdense lesion suggestive of intra-orbital foreign body. In this condition of imaging dilemma, surgical exploration was decided since there was no improvement in clinical symptoms via lateral orbital approach. Two small wooden pieces were detected in orbital exploration. This case highlights the role of history taking, clinical judgement in all cases of intraorbital tumour more so in paediatric population than solely going by the investigative modalities.